Antibacterial characterization of erythorbyl laurate against Geobacillus stearothermophilus spores. (1st February 2022) - Shin, Hyukjin; Kwon, Chang Woo; Lee, Moon-Won; Yu, Hyunjong; Chang, Pahn-Shick
Abstract: We evaluated the antibacterial activity of erythorbyl laurate (EL) against Geobacillus stearothermophilus and its spore in aqueous medium and in oil-in-water (O/W) emulsion. The effective concentrations of EL required to kill vegetative cells and inhibit spore germination were determined. EL exerted bactericidal effects on the vegetative cells at concentrations of 200 and 1500 ppm in the aqueous and O/W emulsion systems, respectively. In addition, EL inhibited spore germination at 200 and 2000 ppm in the aqueous and O/W emulsion systems, respectively, and treatment with concentrations exceeding 7500 ppm killed spores in the emulsion. The germination inhibition activity of EL was verified by determining the dipicolinic acid release from the spores. The antibacterial activity of EL in canned milk coffee indicated that the viable number of spores decreased with increasing EL concentration. Furthermore, the sporicidal activity of EL was greatly enhanced when the spores were exposed to heat treatment at 121 °C in the commercial milk coffee environment, which implies that EL can be used to control contamination of emulsion-based foods. Highlights: Erythorbyl laurate (EL) activity against G. stearothermophilus spores was investigated. Sporicidal effects in the O/W emulsion were achieved with 7500 ppm EL. Sporicidal activity of EL was enhanced at an elevated temperature (121 °C). It can be used to improve the shelf life and quality of emulsion-based foods.